Pengaruh Penggunaan Media Grafis terhadap Hasil Belajar Siswa pada Pembelajaran PAI di SMP Negeri 4 Percut Sei Tuan - Siregar, Ahmad Hasyim Khusairi; Arlina, Arlina (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The low achievement of Islamic Religious Education (PAI) learning outcomes at SMP Negeri 4 Percut Sei Tuan is partly caused by the use of learning media that are still predominantly verbal and do not facilitate students’ visual needs, so that the process of understanding concepts is not optimal. This study aims to analyze the effect of the use of graphic media on student learning outcomes in PAI learning at SMP Negeri 4 Percut Sei Tuan. The research method uses a quasi-experimental design with a pretest-posttest control group model, involving students of grades IX A and B as research subjects, with instruments in the form of learning outcome tests and observation sheets for learning implementation, while data analysis is carried out through an independent t-test to compare differences in the achievements of the two groups. The results of the study showed a significant increase in the learning outcome scores of the experimental group that received graphic media-based learning, both in aspects of conceptual understanding, analytical abilities, and material retention, which is seen from the difference in the average posttest score which is consistently higher than the control group; this finding is supported by statistical significance indicating that graphic media contributes directly to the effectiveness of knowledge transfer, strengthening visual memory, and cognitive engagement of students during the learning process. Theoretically, this study confirms the relevance of the principle of dual coding and multimedia learning in the context of Islamic Education, while practically it provides a basis for teachers to optimize the use of graphic media as a pedagogical strategy that is able to improve the quality of learning and learning outcomes in a sustainable manner.